2014
DOI: 10.4040/jkan.2014.44.6.743
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis in the Prevalence of Type 2 Diabetes According to Risk Factors among Korean Adults: Based on the 2001~2009 Korean National Health and Nutrition Examination Survey Data

Abstract: Purpose: The objective of this study was to provide a trend analysis of the prevalence of diabetes relative to the socioeconomic, lifestyle, and physiologic risk factors among Korean adults aged over 30 years for a 10-year period using data from the Korean National Health and Nutrition Examination Survey. Methods: Prevalence difference and the slope index of inequality were calculated for each risk factors using binomial regression by considering the repeated cross-sectional features of the data. The prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
2
7
0
1
Order By: Relevance
“…A cross-sectional national survey from Malaysia in 2001 showed that among elderly diabetic subjects in Malaysia, 65.2 % were aware of their status, 57.1 % had been treated and only 12.4 % had their diabetes controlled, which is slightly lower than our result [ 18 ]. Data from Korean National Health and Nutrition Examination Survey showed that the prevalence of diabetes increased from 16.4 to 20.3 % for elderly people, which was similar to our results [ 19 ]. A meta-analysis regarding the trends in prevalence, awareness, treatment, and control of diabetes mellitus in mainland China showed the pooled awareness, treatment, and control rate of diabetes were 45.81 %, 42.54 %, and 20.87 % for the general population.…”
Section: Discussionsupporting
confidence: 91%
“…A cross-sectional national survey from Malaysia in 2001 showed that among elderly diabetic subjects in Malaysia, 65.2 % were aware of their status, 57.1 % had been treated and only 12.4 % had their diabetes controlled, which is slightly lower than our result [ 18 ]. Data from Korean National Health and Nutrition Examination Survey showed that the prevalence of diabetes increased from 16.4 to 20.3 % for elderly people, which was similar to our results [ 19 ]. A meta-analysis regarding the trends in prevalence, awareness, treatment, and control of diabetes mellitus in mainland China showed the pooled awareness, treatment, and control rate of diabetes were 45.81 %, 42.54 %, and 20.87 % for the general population.…”
Section: Discussionsupporting
confidence: 91%
“…The overall prevalence of T2DM for adult Chinese (7.9 %; 95 % CI 6.7 % – 9.0 %) was lower than the worldwide prevalence of T2DM in men (9.8 %; 95 % CI 8.6 % –11.2 %) and women (9.2 %; 95 % CI 8.0 % –10.5 %) in 2008, and the prevalence of T2DM in Bangladesh in 2011 (9.2 %), Korea in 2009 (11.8 %), and in the US in 2011–12 (12.4 %), but higher than that in the Netherlands in 2013 (4.4 %), in Australia in 2011–12 (4.6 %; 0.6 % for T1DM and 3.9 % for T2DM), and in India in 2011 (5.1 %; 62.4 million) . A recent national study in 2010 in China reported a prevalence of total diabetes of 11.6 % .…”
Section: Discussionmentioning
confidence: 87%
“…In a recent global study, the International Diabetes Federation (IDF) estimated that from 2013 to 2035 the global number of people with diabetes mellitus is expected to increase from 382 to 592 million, with the number of Chinese people with diabetes increasing from 98.4 to 142.7 million . Several large national health surveys have demonstrated an increase in the prevalence of type 2 diabetes mellitus (T2DM) from 9.8 % to 12.4 % from 1988–94 to 2011–12, respectively, in the US, from 3.74 % to 7.25 % in males and from 2.28 % to 4.88 % for females from 1994 to 2006 in the UK, from 4.1 % to 4.4 % from 2010 to 2013 in the Netherlands, from 7.7 % to 11.8 % from 2001 to 2009 in Korea, from 3.0 % to 14.0 % in males and from 7.9 % to 15.9 % in females from 1997 and 2007 in Japan, and from 1.9 % to 5.6 % from 1993 to 2003 in China . The 2010 Global Burden of Disease Study concluded that the proportion of disability‐adjusted life years from diabetes increased from 1.1 % in 1990 to 1.9 % in 2010 worldwide and from 1.2 % to 2.5 %, respectively, in China .…”
Section: Introductionmentioning
confidence: 99%
“…[12] 낮은 사회경제적 지위의 여성에서 남성보다 비만이 많으며 [17,18], 여성에서도 육체노동자가 비육체노동자 보다 비만율이 높은것으로 보고되었다 [7]. 이를 2) 연구대상자의 제 2형 당뇨병 유병율을 확인한다.…”
Section: 즉 비만은 제 2형 당뇨병의 유의한 위험요인인데unclassified